'The same as everyone else': how academically successful indigenous secondary school students respond to a hidden curriculum of settler silencing. Issue 1 (2nd January 2019) - MacDonald, Liana
ABSTRACT: The paper examines how indigenous Māori students who are striving for academic success in state secondary schools are affected by a hidden curriculum of settler silencing. In this hidden curriculum, the meanings and effects of race are muted through state education policies and school initiatives that claim to support Indigenous youth by attending to culture and ethnicity. The schooling experiences of four high-achieving indigenous girls in this paper show how silencing through cultural and ethnic approaches construct indigenous youth identities in ways that maintain white normativity, particularly as they strive to be academically successful. The girls respond to covert attacks on their personhood by appealing to the demands of white privilege. In this respect, the youth open up spaces within the hidden curriculum to 'speak back' to state constructions of indigeneity and ethnic and cultural difference.